Strategic directions for transition to adulthood for patients with spina bifida - Berry, Jay G.; Kusminsky, Matthew; Foley, Susan M.; Hobbs, Nedda; Queally, Jennifer T.; Bauer, Stuart B.; Kaplan, William J.; Weitzman, Elissa R. (Journal of Pediatric Neurology, 2013)
Although 85% of children with spina bifida survive to adulthood, there is little information and few proven service practices to guide their healthcare transition (HCT) to adult care. Our objective was to deepen our understanding of the factors that facilitate the HCT experience of these patients. Individual interviews with patients with spina bifida (n = 15) and their parents (n = 14) were performed to investigate levels of HCT readiness, attitudes, and practices. Data were analyzed for themes that mapped to theory-based constructs and synthesized as strategic directions for tailoring services. Patient age averaged 18.0 ± 2.8 yr (range 14–28 yr). Factors common to youth who were progressing toward HCT included individual factors: higher cognitive functioning, strong interest in being independent from parents; family factors: exposure to a parenting style that fostered independence; service factors: success negotiating primary care responsibilities with familiar adult healthcare providers. Factors common to youth who were not progressing towards HCT included individual factors: lower cognitive ability, impaired physical ability; family factors: lack of parent awareness of medical transition needs, and, service factors: strong dependence on pediatric providers for care coordination, and negative experiences with adult specialists perceived as not anticipating their needs. Tailoring HCT for individuals with spina bifida may be best done in conjunction with HCT readiness assessments conducted at intervals throughout the HCT period. These assessments should include current and projected cognitive functioning; dyadic support to align patients and parents around HCT goals and care coordination tasks; and methods to familiarize patients and families with adult providers.
Keywords: Spina bifida; healthcare transition to adulthood; children with special healthcare needs; care coordination